(3fgGjI GdhUhd aj Yde GdCUhds - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3JHJOF HGdbSe GdKGfi ai chfg JYGdi HGbjG s
(3BNQgG (B:s
(3JfJgi Hbhdg (B" (3bhdg Ef CHG HcQ eG cGf UGdMkG ddEeGeI , bdfG dGfSde (B" (3ef GdeSCdI GdYGTQI ai EeGeI CHj HcQ s
(3cJHJ ai MjGI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B8 - (3U (B253 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3CUhd Gdabgs